Virtual Inertia from Distributed Pv Converters - Chavez-Orostica, H; Fuentes-Parra, C; Lismayes-Aguilar, A (Institute of Electrical and Electronics Engineers Inc., 2019)
The integration of distributed PV (Photovoltaic) has fostered various concerns on the operation of power systems. One important concern in the lack of frequency response of the PV converters, given the absence of rotating mases of such converters. Although virtual inertia schemes are being proposed, most approaches consider large-scale PV inverters. This work analyses the impact of virtual inertia from distributed PV converters. A simulation with an empirically-validated power system model is considered. © 2019 IEEE.